Meningkatkan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam Pokok Bahasan Mengenal Ketentuan Shalat dengan Menggunakan Strategi Peer Lesson pada Siswa Kelas IV SDN Malei Tojo - Nurjannah Nurjannah (Universitas Pendidikan Mandalika, 2020)
Many obstacles faced in the implementation of Islamic religious education teaching, including (a) teacher factors that still use the old way (traditional) in the learning process. The teacher is fixated on the cognitive field so the assignments given to children far exceed their abilities; (b) discrepancy in curriculum content, objectives, methods and evaluation. The result is a decrease in the quality of teaching Islamic religious education; (c) the Teaching Program Outlines are not explicitly stated about the sequence of assignments that modify the teaching substance, the content of the material, facilities, learning tools and infrastructure. The subjects used in this study were fourth grade students in Malei Tojo Elementary School, West Tojo District. The method in this study uses the method of observation, interviews, documentation and questionnaires with a sample involving 12 respondents. Then with the mean and product moment correlation formula. The effect of the Peer Lesson learning strategy can be said to have a positive influence. This is evident from those obtained by using product moment with an average of 0.566. When consulted with a significant table of 5% and 1%, it can be seen that the value of